Oligonuclear Cobalt Assembly with Schiff-base Ligands - Mikuriya, Masahiro; Naka, Yuko; Handa, Makoto; Tsuboi, Motohiro (Advance Sustainable Science Engineering and Technology, 2026)
In order to develop molecular magnetic compounds, oligonuclear cobalt complexes with Schiff-base ligands, 1,3-bis(salicylideneamino)-2-propanol (H3salpr), 1,3-bis(5-chlorosalicylideneamino)-2-propanol (H3clsalpr), 1,3-bis(5-bromosalicylideneamino)-2-propanol (H3brsalpr), and 1,3-bis(5-nitrosalicylideneamino)-2-propanol (H3pnsalpr), were synthesized by reaction of cobalt(II) acetate and Schiff-base ligand in organic solvent. The molecular structures of [CoII{CoIII(µ-HL)(µ-CH3COO)(CH3COO)}2] (HL = Hsalpr and Hbrsalpr), [CoII{CoII(µ-Hsalpr)(µ-CH3COO)}2], and [CoIII2CoII4(µ-L)2(µ3-CH3O)2(µ-CH3O)6(CH3OH)2] (L = salpr, clsalpr, brsalpr, and pnsalpr) were elucidated by the single-crystal X-ray crystallography. The electronic spectra and magnetic susceptibilities with variable-temperature are in accordance with the trinuclear and hexanuclear molecular structures. The cyclic voltammograms are basically featureless, giving a clue to isolate reduced complexes [CoII{CoII(µ-Hsalpr)(µ-CH3COO)}2] and [CoII2(Hpnsalpr)2(CH3OH)]. These findings may guide future design of molecular magnet materials.